Research on the Performance Improvement Method for Lithium-Ion Battery in High-Power Application Scenarios - Pengfei Zhou; Liying Zhu; Dawei Fu; Jianguo Du; Xinze Zhao; Bingxiang Sun (Energies, 2024)
With the development of technology, high-power lithium-ion batteries are increasingly moving towards high-speed discharge, long-term continuous output, instantaneous high-rate discharge, and miniaturization, and are being gradually developed towards the fields of electric tools, port machinery and robotics. Improving the power performance of batteries can be achieved from multiple dimensions, such as electrochemical systems and battery design. In order to improve the power performance of lithium-ion batteries, this paper proposes design methods from the perspective of electrochemical systems, which include increasing the high-rate discharge capacity and low impedance of the battery. This article also studies the preparation of high-power lithium-ion batteries. This article aims to improve the rate performance of batteries by studying high-performance cathode materials, excellent conductive networks, and high-performance electrolytes. This article successfully screened high-performance cathode materials by comparing the effects of different particle sizes of cathode materials on electrode conductivity and battery internal resistance. By comparing the effects of electrolyte additives under pulse cycling, high-quality electrolyte additive materials were selected. By comparing the effects of different types, contents, and ratios of conductive agents on electrode conductivity, battery internal resistance, high-quality conductive agents, and appropriate ratios were selected. Finally, a 10 Ah cylindrical high-power lithium-ion battery with a specific energy of 110 Wh/kg, pulse discharge specific power of 11.3 kW/kg, an AC internal resistance of ≤0.7 m Ω, a 10C full capacity discharge cycle of over 1700, a 30C full capacity discharge cycle of over 500, and a continuous discharge capacity of 10C–30C, and a pulse discharge capacity of over 100C was prepared.